Simulação termodinâmica de um sistema robótico de inspeção - Gund, Jefferson (2022)
The Oil and Gas industry uses many equipment for extraction and processing that need periodic maintenance to ensure the safety of plant operations, considering that accidents can result in serious and irreversible damages to the environment and people. Due to the unhealthy environment found and the necessity of stopping the operation of these equipment to allow access for inspectors, the use of robot-assisted inspection methods becomes advantageous. In order to comply with this need, the Laboratory of Automation and Advanced Control Systems (LASCA) at UTFPR Campus Curitiba, developed a robotic inspection system. The robot was designed for autonomous operation, to ensure the physical integrity of the components, considering the high operating temperatures of the equipment to be inspected. This research develops an investigation of the thermodynamic behavior of the robot and the ultrasonic inspection system through a computer simulation approach, by using computer models of the robot in three cartesian dimensions and applying the Finite Element Method (FEM) to calculate the heat balance. As a result of this work, temperature curves were obtained for different points of the robot, as well as temperature gradients for the Ultrasound Inspection System. This result made it possible to estimate, while in the conceptual design phase of the robot, the maximum time of using this in different conditions of temperatures on the surface of the tank, in addition to providing subsidies for the development in ultrasound’s researches for non-destructive inspection, applied to high temperatures.